In vitro effects of natural prenyloxycinnamic acids on human cytochrome P450 isozyme activity and expression - Genovese, Salvatore; Epifano, F.; Curini, M.; Menger, Dominic; Zembruski, Nadine Cécile Luise; Weiß, Johanna (Phytomedicine, 2011)
Previous studies demonstrated that natural prenyloxyphenylpropanoid derivatives have potent biological properties like anti-cancer effects in vitro and in vivo. Additionally they are extremely safe and associated with low toxicity, making them excellent candidates as chemopreventive agents. However, so far only little is known about possible interactions with isoforms of cytochrome P450 (CYPs) being involved in the metabolism of xenobiotics and representing a major site for drug-drug interactions. The aim of this study was to evaluate the effects of selected natural prenyloxyphenylpropanoids (prenyloxycinnamic acids) on expression and activity of some major CYPs and on the activity of the major drug efflux transporter P-glycoprotein (P-gp). Inhibition of CYP3A4, CYP2C19, and CYP2D6 was quantified using commercially available kits. P-gp inhibtion was quantified by calcein assay. Induction of CYP mRNA (CYP3A4, CYP2C19, CYP2C9, and CYP2B6) was measured in LS180 cells by quantitative real-time reverse transcriptase polymerase chain reaction using the LightCycler technology. Only boropinic acid revealed substantial inhibition of CYPs, especially of CYP2C19 (IC50=31±5μM). This compound also had the most pronounced effect on CYP mRNA expression among the prenyloxycinnamic acids tested. However all but 4′-isopentenyloxy-p-coumaric acid revealed inducing effects on CYPs with different induction profiles. P-gp was only significantly inhibited by 4′-geranyloxyferulic acid. This was the first study demonstrating modulating effects of prenyloxycinnamic acids on CYP activity and expression and on P-gp activity. The results suggest that boropinic acid is most prone to drug-drug interactions at the level of CYPs, whereas 4′-isopentenyloxy-p-coumaric acid does not modulate CYP activity and expression.
Gesehen am 30.10.2023
Online verfügbar am 26. November 2010